Reduction of 4-nitrophenol using copper loaded surfactant-modified chitosan beads: An approach towards sludge management. (August 2022) - Nath, Ankurita; Biswas, Subhadeep; Pal, Preeti; Pal, Anjali
Abstract: Chitosan hydrogel (CS) beads and surfactant-modified chitosan hydrogel (SMCS) beads are used for the removal of Cu(II) ions from aqueous solution. After removal of metal ions, the waste Cu(II) ion-adsorbed beads have been used as an efficient catalyst for the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) in aqueous NaBH4 . This approach can be considered as a part of 'zero waste management practice'. The first step of the present work deals with the preparation of CS hydrogel beads with their further modification using anionic surfactant e.g. sodium dodecyl sulfate (SDS) at a concentration greater than the critical micelle concentration (CMC). This step leads to the formation of SMCS beads. In the second step, the CS and SMCS beads are used to remove Cu(II) ions from aqueous solution. The Cu(II) ion-loaded CS beads are designated as Cu-CS beads, and the Cu(II) ion-loaded SMCS beads are named as Cu-SMCS. These beads can be recognized as waste (or spent) beads. The Cu(II) ion removal efficiency and the calculated Cu(II) loading of SMCS beads are very similar to that of normal CS beads. In the third step these waste Cu-CS and Cu-SMCS beads have been utilized as a catalyst to reduce 4-NP to 4-AP in presence of borohydride. The 4-NP reduction using Cu-CS and Cu-SMCS follows zero order kinetics at varying catalyst doses in the range of 0.2–0.6 g/L, and at varying 4-NP concentrations in the range of 4 × 10 −5 – 1.2 × 10 −4 M. However, at all the doses the induction time required to start the reduction is higher in case of Cu-CS than Cu-SMCS beads. It is interesting to observe that, at a catalyst dose of 0.2 g/L and under identical condition, the Cu-SMCS beads act as a much better catalyst compared to the Cu-CS, and the zero order rate constant obtained with Cu-SMCS as the catalyst is found to be 30 times higher compared to that obtained using Cu-CS. This is due to the synergistic effect offered by the surfactant bilayer present on the surface of Cu-SMCS. The characterization of the Cu-SMCS beads has been done using XRD, SEM, EDAX, FTIR analyses. The turnover number (TON) and turnover frequency (TOF) of Cu-SMCS are compared with other reported catalysts, and they are found comparable. Thus waste Cu-SMCS beads have been proved to be an effective catalyst for 4-NP reduction. Graphical Abstract: ga1